Neurophysiological findings from magnetoencephalography in autism spectrum disorder: a comprehensive review. (May 2014) - Lajiness-O'Neill, Renee; Bowyer, Susan M; Moran, John E; Zillgitt, Andrew; Richard, Annette E; Boutros, Nash N
ABSTRACT: : Autism spectrum disorder (ASD) is an etiologically and clinically heterogeneous group of neurodevelopmental disorders, diagnosed exclusively by the behavioral phenotype. The neural basis of altered social, communicative, somatosensory, and restricted and repetitive behaviors remains largely unknown. Magnetoencephalography (MEG) provides a vital method of inquiry to identify the neurophysiological mechanisms of ASD, better illuminate etiologically distinct subgroups, understand the developmental trajectories of aberrant connectivity and track outcome. MEG is a neuroimaging methodology that can localize sources of electrical activity within the brain with millisecond resolution by noninvasively measuring the magnetic fields arising from such activity. This review addresses the central MEG findings exploring auditory, visual and somatosensory processing, higher-order/executive functioning, and resting state in individuals with ASD over the past decade and a half. We offer a summary of emerging trends related to neurophysiological alterations, aberrant hemispheric specialization and connectivity, as well as limitations in the literature and recommendations for future MEG investigations.